Recent advances in the commercial formulation of arbuscular mycorrhizal inoculants - Ghorui, Maunata; Chowdhury, Shouvik; Burla, Sashidhar (Frontiers in Industrial Microbiology, 2025)
The global agricultural sector faces significant challenges due to increasing demands from a growing population, limited arable land and the environmental degradation caused by chemical inputs. As a potential solution, microbial inoculants, particularly arbuscular mycorrhizal fungi (AMF), offer an eco-friendly alternative to traditional fertilizers and pesticides. AMF enhance plant growth by improving nutrient and water uptake while protecting against stressors, fostering sustainable agriculture. This study explores the production, development, and application of AMF bioformulations, emphasizing key requirements for their effectiveness, including strain selection, genetic stability, environmental compatibility, other beneficial microbial compatibility, and eco-friendly carriers. Advances in production methods such as substrate-based systems, bioreactors, and solid media are discussed, along with the role of synergistic microbial combinations to enhance agricultural productivity. Additionally, challenges in the stability, shelf-life, and quality control of AMF bioformulations are addressed, with a focus on adjuvants, fillers, and storage methods. Risk evaluation and biosafety concerns related to the use of novel microbial strains are examined, particularly in the context of regulatory frameworks that classify bioformulations as biostimulants or biopesticides. Barriers to widespread adoption, including farmer awareness, product quality, and regulatory constraints, are identified. Despite these obstacles, the potential of mycorrhizal inoculants for sustainable agricultural practices remains high, provided that ongoing research, development, and collaboration between stakeholders can address these challenges.